Effectiveness of Grouting and GFRP Reinforcement for Repairing Spalled Reinforced Concrete Beams - Achmad Z. Mansur; Rudy Djamaluddin; Herman Parung; Rita Irmawaty; Daud Nawir (Civil Engineering Journal, 2024)
Corrosion of steel reinforcement from chloride exposure can compromise the strength of reinforced concrete structures. Rust formation expands, applying pressure on concrete, resulting in cracks and spalling. Prompt repair is crucial for severe cases of spalling. This research assessed the efficacy of repair strategies for reinforced concrete beams post-spalling, including grouting and different techniques involving Glass Fiber Reinforced Polymer (GFRP) reinforcement. The research examined four variations of reinforced concrete beams, each sized at 150 mm × 200 mm × 3300 mm. Results showed that the standard beam (BK) had an average maximum load capacity of 29.74 kN. In contrast, the grouted beam (BGR) demonstrated a reduced maximum load of 14.39 kN, along with decreased steel and concrete strain compared to BK. This suggests that the grouting repair did not fully restore the beam's flexural capacity after spalling. Incorporating GFRP strips (BGRS) led to a marginal increase in the beam's maximum load, albeit remaining below BK, with lower steel and concrete strain than BK. However, the steel and concrete approached their yield points, indicating enhanced flexural performance. The full-wrap GFRP beam (BGRSF) experienced an 8.08% increase in maximum load compared to BK, with concrete strain surpassing BK, suggesting an enhancement in flexural stiffness. Doi: 10.28991/CEJ-2024-010-07-05 Full Text: PDF